A novel inducible complement C3 conditional knockout mouse model: Generation and characterization: Developing topics. (7th December 2020) - Batista, Andre Felipe; Schroeder, Maren; Khan, Khyrul; Yalcin, Esra; Carroll, Michael; Lemere, Cynthia A
Abstract: Background: The classical complement pathway is a complex process involved in the elimination of dead cells, debris, and pathogens, and as well as brain wiring during development. Complement protein C3 is an innate immune molecule central in the complement pathway. It participates in removing pathogens and eliminating synapses, and is elevated with aging and neurodegenerative diseases, including Alzheimer's Disease. Previously, we showed that lifelong, germline C3‐deficiency protected aged male wild‐type and APPswe/PS1dE9 mice against hippocampal neuronal dysfunction and cognitive decline, despite increasing the Aβ plaque load. However, it remains unknown whether suppressing complement C3 signaling during early stages of AD pathogenesis, when relevant therapeutic interventions might be considered, would confer neuroprotection. Method: To address this question, we generated the first‐ever C3 floxed (C3 fl/fl ) mouse line, and then crossed the C3fl/fl mice with an inducible, global Cre line (Rosa26‐Cre‐ERT2 +/‐ ) for 2 generations to generate novel inducible C3 conditional knockout C3 fl/fl ; Rosa26‐Cre‐ERT2 +/‐ mice. Mice aged 2‐3 months received intraperitoneal injections of either corn oil or tamoxifen (75 mg/kg) once a day for 5 consecutive days. We analyzed the C3 serum levels at 7, 14, 30, 60, and 90 days post‐tamoxifen treatment. We also analyzed the mRNA expression of complement C1q and C3 in the brain and liver 60 days following tamoxifen treatment. Result: C3 fl/fl ;Rosa26‐cre‐ERT2 +/‐ mice had a significant 70% reduction in serum C3 levels compared to controls, which was consistent at all timepoints analyzed. We also showed that C3 expression in the liver, the main source of complement proteins, as well as in the brain was reduced, demonstrating effective recombinase activity in these organs. Intriguingly, C1q mRNA expression was increased in the brain and liver following tamoxifen treatment; further studies are underway. Conclusion: In conclusion, we present a novel mouse model in which tamoxifen treatment resulted in sustained lowering of C3 in the serum, liver, and brain. We will next cross this model with AD‐like mouse models of amyloidosis and tau pathology to evaluate whether global C3 lowering in early stages AD pathogenesis is protective and if so, our data would support targeting complement as a therapy for AD.